Analisis Struktur Lagu Biar Menjadi Kenangan Ciptaan Ahmad Dhani - Althoof Ardena Reki; Yensharti Yensharti (SENDRATASIK UNP, 2020)
This study aims to analyze and describe the song Biar Menjadi Kenangan. The type of this research is a qualitative research with a content analysis approach. The theory used wasanalyzing the song structure and form. The data were collected through literature study, observation, and labor work. Based on the analysis of the song Biar Menjadi Kenangan, it is found that the structure / form / period of the song Biar Menjadi Kenangan consists of 3 major parts, namely A, B, and C with periods A, A, B, C, A ', B, C, A ', B, C and C, while the phrases found are A (a, x) A (a, x) B (b, y) C (c, z) A (a, x') B (b, y) C ( c, z), A (x '), B (b, y), C (c, z) and C (c, z). Meanwhile, the motif processing is formed from m, n, and o motifs which are formed by 12 motifs.